2022
DOI: 10.3390/jcm11092278
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Single-Stage Correction by Posterior Approach for Neglected Congenital Scoliosis: Comparative Analysis According to the Age of Surgical Intervention

Abstract: Background: A single-stage correction for congenital scoliosis through a posterior-only approach is a commonly used surgical technique. However, there are few studies on the surgical treatment effect of posterior single-stage correction in patients with neglected congenital scoliosis. Methods: Patients who underwent a single-stage posterior correction for congenital scoliosis with a minimum follow-up of 2 years were divided into three groups based on age: Group A (7–11 years), B (12–18 years) and C (>18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…The literature describes a strong correlation between the curve correction and improvement in PF (Table 5). Improving respiratory function before surgery for elective scoliosis correction may reduce the risk of postoperative complications [14,29]. In our study, we arrived at similar conclusions.…”
Section: Hrqol Pf and Sfsupporting
confidence: 83%
See 2 more Smart Citations
“…The literature describes a strong correlation between the curve correction and improvement in PF (Table 5). Improving respiratory function before surgery for elective scoliosis correction may reduce the risk of postoperative complications [14,29]. In our study, we arrived at similar conclusions.…”
Section: Hrqol Pf and Sfsupporting
confidence: 83%
“…A considerable percentage (28%) of our patients in the MG group preoperatively rated BP as moderate to severe, which is similar to other studies by Ramirez et al, who noted that 23% of patients with AIS were noted with BP at the time of diagnosis [47], and Sieberg et al, who showed that, of 190 patients with AIS, 35% reported moderate to severe pain preoperatively [48]. Some studies have described the prevalence of BP in AIS patients before surgical treatment as being from 42% to 80% [23,[48][49][50][51][52], but the prevalence of BP in patients with AIS and its relation to spinal deformity remains unclear [14,15,17,52]. In our study, there was no noted statistical difference in the back pain between patients managed with HGT, TID, and IT (p < 0.001).…”
Section: Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…During the eighth to ninth year of life, flexibility increases significantly due to progressive growth and adaptation of the musculoskeletal system ( Zhang et al, 2023 ). This increased flexibility allows 8–to 9-year-olds to perform a wider range of movements while reducing the risk of overuse or injury ( Yang et al, 2022 ; Behm et al, 2023 ; Zvetkova et al, 2023 ). Activities that promote flexibility, such as stretching and yoga, can help maintain healthy joints and muscles while promoting awareness of the importance of regular physical activity (PA) ( Chan et al, 2023 ; Y; Cho et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%